(untitled) (Canadian Dermatology Today, 2024)
The anti-IL-17 class is not only highly effective in treating psoriasis, but also other comorbidities associated with type 2 inflammation. Data presented by Dr. Kim Papp at the European Academy of Dermatology and Venerology in 2022 shows that brodalumab (Siliq), in particular, can effectively treat psoriasis even among patients for whom other IL-23- and IL-17-targeting biologics don’t work or have lost effectiveness over time. However, Brodalumab’s black box warning can be a prescribing barrier, especially among new-to-practice physicians. In this roundtable discussion, Dr Anatoli Freiman and Dr Susan Poelman, who both have wide clinical and research expertise in biologic therapies for psoriasis, share how they weigh clinical and real-world data of IL-17 cytokine inhibitors (secukinumab, ixekizumab, & bimekizumab) and IL-17 receptor antagonists (brodalumab) when treating psoriasis.